Effect of Selected Group of Asanas on the Patients with Cervical Vertigo - Samriti; Kumar, BMN; Tripathi, JS (International Research Journal of Ayurveda & Yoga, 2023)
One of the most prevalent issues among patients in their middle years is vertigo. The existence of so-called cervical vertigo among the different causes of dizziness is still debatable. Based on the research of cervical vertigo was once believed to be caused by aberrant input from cervical sympathetic nerves. Later studies discovered that sympathetic stimulation has no effect on cerebral blood flow. Some studies made the hypothesis that diseases of vertigo of cervical origin can be associated to aberrant sensory input from the damaged joint receptors of upper cervical areas. Additional research revealed that cervical intervertebral disc disease appears to be the source of cervical vertigo. According to recent studies, vertigo of cervical origin may be associated to the in growth of many Ruffini corpuscles into degenerative cervical discs. Generally, the symptoms of Vertigo are not visible at the initial time, some time people consider it as epilepsy or brain related disease, first of all, it is necessary to diagnose and treat it properly. Yoga is an alternative therapy for any kind of cervical related problems, in which some special Asanas like Bhujangasana, Dhanurasana, Makarasana, Ardhamatsyendrasana, Akaranadhanurasana and Pranayama such as NadiShodhan, Bhramari, and Udgeetha. Which is helpful in this type of pain, it has been seen from many studies that yoga may work as a shield for spinal card related problems.